Analisis Kualitas dan Indeks Pencemaran Air pada Usaha Budidaya Perikanan di Desa Kota Karang Kecamatan Kumpeh Ulu Kabupaten Muaro Jambi - Pujianto, Pangestu Eko; Suryono, Suryono; Afriani, Afriani (Universitas Batanghari Jambi, 2024)
This research aims to analyze the quality of freshwater cultivation and analyze the pollution index for freshwater cultivation in Desa Kota Karang, Kec. Kumpeh Ulu, Kabupaten Muaro Jambi. This research uses quantitative analysis techniques. The results of analysis and water quality tests concluded that the cultivation ponds in Desa Kota Karang were in the lightly polluted category. Based on research conducted on 10 ponds, there were 3 ponds that met quality standards, the rest were in the lightly polluted category. This is based on tests and analysis of physical, chemical and biological parameters. Meanwhile, the results of the pollution index analysis obtained IP values ranging from 0.88 to 2.91. According to PP Number 22 of 2021, if 1 < IP ≤ 5 then the cultivation pond in Desa Kota Karang is in the lightly polluted category. Based on the results of the air quality analysis and pollution index, the air quality in the cultivation ponds in Kota Karang Village is still suitable for use for fish cultivation. Therefore, it is necessary to carry out further monitoring and recovery efforts for BOD and COD parameters that have exceeded class III quality standards of PP Number 22 of 2021 concerning Freshwater Fisheries Cultivation, so that ponds in Desa Kota Karang remain safe for carrying out cultivation activities.